2012
DOI: 10.3171/2012.1.peds11453
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up imaging to detect recurrence of surgically treated pediatric arteriovenous malformations

Abstract: Object The true postoperative incidence of arteriovenous malformation (AVM) recurrence in the pediatric population remains largely unreported. Some literature suggests that delayed imaging studies should be obtained at 6 months to 1 year after negative findings on a postoperative angiogram. The aim of this study was to describe the timing of AVM recurrences after resection and the neuroimaging modalities on which the recurrences were detected. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 26 publications
(43 reference statements)
3
71
0
Order By: Relevance
“…16 This finding lends support to the concept that delayed postoperative DSA is needed to monitor for recurrent AVM in children. However, it should be noted that long-term follow-up in our series identified 1 patient with a recurrence 6 years after complete resection with a previously negative surveillance DSA at 4 years (Case 3), as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…16 This finding lends support to the concept that delayed postoperative DSA is needed to monitor for recurrent AVM in children. However, it should be noted that long-term follow-up in our series identified 1 patient with a recurrence 6 years after complete resection with a previously negative surveillance DSA at 4 years (Case 3), as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 63%
“…3,6,24,28 Accumulating evidence has demonstrated that AVMs recur in children. 1,2,14,16 The rate of hemorrhage associated with recurrent AVMs is not well defined, largely due to relatively small numbers of patients available for study. We confirm in our series that recurrences do occur in the pediatric population, and demonstrate that they can present with hemorrhage despite recent negative imaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations